Development, Acceptability, and Initial Implementation of an Interactive Text-Messaging Program for Fathers with Low Income - Lee, Joyce Y.; Lee, Shawna J.; Xu, Amy; Steinke, Hannah; Weiland, Christina (Maternal and child health journal, 2024)
Objectives This study describes the development, acceptability, and implementation of an interactive text messaging program to engage fathers enrolled in home visitation programs. Methods We used an iterative development approach that integrated rapid testing of intervention content with acceptability feedback from program participants to examine the processes of implementation. In Study 1, we describe the rapid testing framework and present data from 171 men who provided feedback on Text4Dad content via three online surveys. In Study 2, a case study, we use administrative data from 108 fathers with whom we pilot-tested Text4Dad in three community-based home visiting programs, with the program implemented by fatherhood program community health workers (F-CHWs). Content analysis of exchanges between F-CHWs and fathers describes the specific use of Text4Dad. Results Across all three online surveys, fathers reported positive reviews of the Text4Dad content. The F-CHWs used Text4Dad mainly to push out information, especially that related to home visit scheduling and local events, instead of engaging in bidirectional interactions with fathers. Conclusions for Practice We conclude with a set of recommendations for social service and maternal and child health providers regarding the feasibility of implementing text messaging to support home visiting in community-based settings. Significance What is Already Known on this Subject? In leveraging mobile technology for behavioral change, there has been a proliferation of text messaging parenting interventions. Innovative texting and technology-focused programs for fathers have been developed and implemented, with a focus on improving fathering quality, father-child interactions, program fidelity, and measures relevant to the duration, timing, and context of programs. That said, the effectiveness of these programs has been challenging to ascertain and compare, given and unique programmatic aspects of each intervention and lack of robust program evaluation designs. What this Study adds? Most father-inclusive text messaging interventions are stand-alone programs. Importantly, Text4Dad is one of the first programs to serve as an add-on to an existing community-based home visitation model, with the goal of engaging fathers who are from low-income contexts and receiving in-home visits. This initial implementation study shows the promise of a low-cost and mentor-based text messaging program that is appealing and useful for fathers and male CHWs serving them.